The impact of Ghana's entrepreneurial ecosystem on women's entrepreneurial performance: the moderating role of entrepreneurial identity - Akuamoah Boateng, Irene (Rhodes University, Faculty of Commerce, Rhodes Business School)
Women business leaders are generating a tremendous impact in their markets, industries and communities through innovation, job creation and economic growth. However, their contributions are often lost in the prevailing narrative that women are over-represented among the poorest and most vulnerable entrepreneurs globally. A review of the extant literature has postulated challenges that women entrepreneurs faced several challenges in the ecosystem in which it operates. Women entrepreneurs have access to limited capital as compared to its men counterparts, fewer opportunities to network and build relationships with other entrepreneurs, investors, and mentors, which affects their access to resources and knowledge. Due to the issue of gender-based stereotypes and biases that women entrepreneurs constantly face, they are unable to meet mentors who can provide them with guidance and support to grow their business. These women-specific challenges have become barriers limiting the growth of women entrepreneurs, however insufficient reports highlight how these hindering factors can create opportunities for the growth of women entrepreneurs. Dwelling on the Process theory, the study explored the impact of Ghana's entrepreneurial ecosystem on women's entrepreneurial performance with the moderating role of entrepreneurial identity. The study was a cross-sectional quantitative research design with data collected from 413 women entrepreneurs in the Greater Accra Region using structured questionnaire collected using the survey monkey online tool. The data was analyzed using IBM SPSS v.25 and the PLS-SEM v.4.0. The first objective was examined through 12 hypotheses, while the second was analyzed using 2.The study finds that access to finance has positive and insignificant effect on the entrepreneurial performance of women in Ghana. Likewise, education and training have a negative and insignificant effect on the market and operational performance of women entrepreneurs in Ghana. The results of the study postulated that the availability of infrastructure and resources has a negative but significant effect on both the market and operational performance of Ghanaian women entrepreneurs. The results of the study further reported a positive but insignificant impact of network and social capital on the market performance and operational performance of women entrepreneurs in Ghana. The results of the study in relations to the regulatory environment and women entrepreneurial performance indicates an insignificant relationship between regulatory environment and market performance and regulatory performance whilst cultural and social factors within the Ghanaian ecosystem negatively but significantly influence the entrepreneurial performance of women in Ghana but innovation and knowledge spillover have a positive and significant impact on both the market performance and operational performance. Furthermore, the findings of the study suggest that Ghana's entrepreneurial ecosystem may not have a substantial direct impact on women's entrepreneurial performance in Ghana. Further practical and theoretical implications of the study are discussed in the thesis.
Keywords: Entrepreneurship -- Ghana; Businesswomen -- Ghana; Identity (Psychology); Entrepreneurial ecosystem; Women -- Economic conditions; Women -- Social conditions